Reframing Experiential Education : A Broader Perspective of Community Engagement - Welch , Marshall (Experiential Learning and Teaching in Higher Education, 2022)
This article invites the reader to reframe the traditional perspective of experiential education to a broader conceptualization of community engagement in which various stakeholders, in addition to students, are the beneficiaries of the learning experience. In addition to acknowledging and celebrating the pedagogical approach, this narrative also provides a friendly critique of our traditional and perhaps somewhat limited perspective of experiential education. Challenges and potential detrimental impact are considered, coupled with approaches on how to minimize those issues.